2010
DOI: 10.1007/s15010-010-0052-x
|View full text |Cite
|
Sign up to set email alerts
|

One-year follow-up of patients of the ongoing Dutch Q fever outbreak: clinical, serological and echocardiographic findings

Abstract: PurposeIn 2007, a large goat-farming-associated Q fever outbreak occurred in the Netherlands. Data on the clinical outcome of Dutch Q fever patients are lacking. The current advocated follow-up strategy includes serological follow-up to detect evolution to chronic disease and cardiac screening at baseline to identify and prophylactically treat Q fever patients in case of valvulopathy. However, serological follow-up using commercially available tests is complicated by the lack of validated cut-off values. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
52
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 30 publications
2
52
1
Order By: Relevance
“…This is in contrast with earlier reports from France, where endocarditis predominates (1, 7). It might be that this disparity is caused by strain-specific differences, leading to distinct clinical presentations (24). Another explanation might be increased awareness in the Netherlands of this previously relatively unacknowledged manifestation of chronic Q fever.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast with earlier reports from France, where endocarditis predominates (1, 7). It might be that this disparity is caused by strain-specific differences, leading to distinct clinical presentations (24). Another explanation might be increased awareness in the Netherlands of this previously relatively unacknowledged manifestation of chronic Q fever.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, active case finding in a Q fever epidemic area could be initiated by screening for Q fever in high-risk groups, including patients with aneurysms, vascular prostheses, or heart valve prostheses (12). In our current analysis, minor heart valve lesions (for example, grade I aortic valve insufficiency) were also included as risk factors for chronic Q fever, although the influence of minor valvulopathies on chronic Q fever development is debated (13,24,25). This could have led to overestimation of the amount of risk factors in all chronic Q fever cases.…”
Section: Discussionmentioning
confidence: 99%
“…Besides chronic Q fever (ie, persistent C. burnetii infection), which occurs in 1%-5% of cases [1], a debilitating fatigue syndrome has been described [2][3][4][5][6][7][8][9][10][11]. This Q fever fatigue syndrome (QFS) persists for years in approximately 20% of cases following acute Q fever [2][3][4][5][6][9][10][11]. Many QFS patients fulfill the case definition of chronic fatigue syndrome (CFS) [2,8,10,12].…”
mentioning
confidence: 99%
“…These titers can also be caused by antibodies cross-reacting to other pathogens or by aspecific reactions (18). Yet, it is also known that, following C. burnetii infection, antibodies to C. burnetii can disappear over time or titers can become very low, leading to an underestimation of the infection rate (12,25). This was illustrated in our study by one case who had a confirmed acute Q fever episode in 2009 and demonstrated a phase II IgG titer of 1:32 in our screening.…”
Section: Discussionmentioning
confidence: 99%